2018
DOI: 10.2147/ijn.s171400
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mycolic acid forms using surface-enhanced Raman scattering as a fast detection method for tuberculosis

Abstract: BackgroundTuberculosis (TB) is the ninth leading cause of death worldwide and the leading cause from a single infectious agent, based on the WHO Global Tuberculosis Report in 2017. TB causes massive health care burdens in many parts of the world, specifically in the resource constrained developing world. Most deaths from TB could be prevented with cost effective early diagnosis and appropriate treatment.PurposeConventional TB detection methods are either too slow as it takes a few weeks for diagnosis or they l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…RS has been widely used to study bacterial biofilms ( Kelestemur et al, 2018 ). It has also been used to study the biology of mycobacteria ( Buijtels et al, 2008 , Kumar et al, 2020 , Perumal et al, 2018 , Stöckel et al, 2017 , Stöckel et al, 2015 , Verma et al, 2019 ). Raman spectroscopy also has potential as a diagnostic tool, as it allows the identification of mycobacteria to the species level ( Buijtels et al, 2008 , Stöckel et al, 2017 , Stöckel et al, 2015 , Verma et al, 2019 ), and even to determine the viability of the identified bacilli ( Kumar et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…RS has been widely used to study bacterial biofilms ( Kelestemur et al, 2018 ). It has also been used to study the biology of mycobacteria ( Buijtels et al, 2008 , Kumar et al, 2020 , Perumal et al, 2018 , Stöckel et al, 2017 , Stöckel et al, 2015 , Verma et al, 2019 ). Raman spectroscopy also has potential as a diagnostic tool, as it allows the identification of mycobacteria to the species level ( Buijtels et al, 2008 , Stöckel et al, 2017 , Stöckel et al, 2015 , Verma et al, 2019 ), and even to determine the viability of the identified bacilli ( Kumar et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the fast and efficient detection of TB, the use of mycolic acids of tuberculin bacilli was also described. This was reported by the use of surface-enhanced Raman scattering (SERS) technique to detect three major forms of mycolic acids which were expressed by mycobacteria [24]. The detection rate of the diseases by the use of small quantity of samples is of paramount importance in cases with TB where the amount of tissue is limited for sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the spectral pattern for all the prominent peaks seen within the 800−1600 cm −1 frequency range of the fingerprint region obtained for wtBCG from the biosensor based studies strongly resembles the SERS spectral pattern typically reported for cell-wall bound mycolic acid lipid profiles, as seen for intact whole cell TB-affiliated mycobacteria. 13 ■ CONCLUSIONS…”
Section: Acs Sensorsmentioning
confidence: 99%